THE NATURE OF CHILDREN'S READING IN CLASSICAL LITERATURE - Jumayeva Dilnoza Tursunpo‘lanovna (Journals Park Publishing, 2023)
This article is dedicated to the giants of children's reading associated with classical literature. The article uses examples of classical Uzbek literature.
Keywords: reading books, classical literature, children's literature, Alisher Navoi, Yassavi Khan, stories, Navoi Khan.